FDA Approval Summary: Sunitinib for the Treatment of Progressive Well-Differentiated Locally Advanced or Metastatic Pancreatic Neuroendocrine Tumors - Blumenthal, Gideon M. (AlphaMed Press, 2012)
On May 20, 2011, the U.S. Food and Drug Administration (FDA) approved sunitinib malate capsules (Sutent®; Pfizer, Inc., New York) for the treatment of progressive, well-differentiated pancreatic neuroendocrine tumors (pNETs) in patients with unresectable locally advanced or metastatic disease. In a phase III randomized trial, 171 patients received either sunitinib (37.5 mg) or placebo once daily. The progression-free survival (PFS) interval was the primary efficacy endpoint. Secondary endpoints included the overall survival (OS) time, objective response rate (ORR), patient-reported outcomes, and safety. Based on early results favoring sunitinib, the independent data monitoring committee recommended trial termination prior to the prespecified interim analysis. This premature analysis may have led to an overestimate of the treatment effect. In the FDA analysis of investigator-assessed PFS times, the median values for the sunitinib and placebo arms were 10.2 months and 5.4 months, respectively. The ORRs were 9.3% and 0% in the sunitinib and placebo arms, respectively. The OS data were not mature at the time of approval and were confounded by 69% crossover. Common adverse reactions in patients receiving sunitinib included diarrhea, nausea, asthenia, fatigue, neutropenia, hypertension, and palmar–plantar erythrodysesthesia syndrome. Two patients on sunitinib died as a result of cardiac failure. The Oncologic Drugs Advisory Committee voted eight to two that, despite residual uncertainty about the magnitude of the PFS effect because of early trial termination, sunitinib demonstrated a favorable benefit–risk profile in pNET patients. The FDA concurred with the committee's assessment and granted sunitinib regular approval for this rare malignancy with few available therapies.